This is the place for me - Cole, Joanna; Van Horn, William (New York : Scholastic, 1986)
Morty the bear is looking for a house, but he has a difficult time finding the perfect one.
2.0
K-3
Keywords: Bears -- Fiction; Dwellings -- Fiction; Bears -- Fiction; Houses -- Fiction